Using Behavioral Science to Design a Peer Comparison Intervention for Postabortion Family Planning in Nepal - Spring, Hannah; Datta, Saugato; Sapkota, Sabitri (Frontiers in Public Health, 2016)
Despite the provision of free and subsidized family planning services and clients’ demonstrated intention to delay pregnancy, family planning uptake amongst women who receive abortion and post-abortion services at Sunaulo Parivar Nepal (SPN), one of Nepal’s largest non-governmental sexual and reproductive health (SRH) providers, remains low. Through meetings, interviews and observations with SPN’s stakeholders, service providers, and clients at its 36 sexual and reproductive health centers, we developed hypotheses about client- and provider-side barriers that may inhibit PAFP uptake. On the provider side, we found that the lack of benchmarks (such as the performance of other facilities) against which providers could compare their own performance, and the lack of feedback on performance were important barriers to PAFP uptake. We designed several variants of three interventions to address these barriers. Through conversations with team members at SPN’s headquarters and service providers at SPN centers, we prioritized one of these interventions, a peer-comparison tool. This peer-comparison tool allowed providers at one center to compare their performance with that of other similar centers. We used feedback from the community of providers on the tools’ usability and features to select a variant of the tool that also leverages and reinforces providers’ strong intrinsic motivation to provide quality PAFP services. In this paper, we detail the process of identifying barriers and creating an intervention to overcome those barriers. The intervention’s effectiveness will be tested with a center-level, stepped-wedge randomized control trial in which SPN’s 36 centers will be randomly assigned to receive the intervention at one-month intervals over a 6-month period. Existing medical record data will be used to monitor family planning uptake.